An organization based cross-sectional study of occupational injuries among bridge construction workers in an urban area of Mumbai - Kaur, Daljeet; Rajan lilare, Rushali; Dilip Rathod, Neeta; Datta, Bibhash; kaswan, Pradeep (International Journal Of Community Medicine And Public Health, 2019)
Background: Occupational injuries are matter of consideration and purport to be raising cost directly like in illnesses and accidents, loss of employment, disability and loss of productivity and subsequently to families and Society. However, there is paucity of studies to elucidate the state of affairs in most of the part of India. The Present study dictates the prevalence of injury and associated factors among Bridge Construction workers in urban area of Mumbai. Objectives are (1) to study prevalence of injury among bridge construction workers, (2) to identify the factors related to such occupational injuries. Methods: A cross-sectional study was conducted among bridge construction workers in urban area of Mumbai from August 2017 to December 2017. Sample size was 150 by convenient method sampling which were selected randomly. Results: The prevalence of injury among Bridge making was 25.7% in past 3 months. Factors like not using protective devices, smoking, tobacco chewing, lack of sleep, work experience were factors associated with suffering. Conclusions: In the study dictating construction workers health and safety in an urban area of Mumbai, where higher prevalence of injury (25.7%) reported in bridge workers in an urban area of Mumbai. If intense mediation are not established then work absenteeism, drooping of work output, occupation related ailments, disabilities and casualties would remain in existence a major problem among construction workers .Therefore programmes to alleviation the load exhibited by construction related injuries should focus on work safety training, monitoring of health and substance abuse in work area.